1992
DOI: 10.1007/bf01625172
|View full text |Cite
|
Sign up to set email alerts
|

A unique case of naturally occurring mummification of human brain tissue

Abstract: When skulls and bones were exhumed from a mass grave in Bulgaria and subjected to medicolegal examination they were found to originate from 39 humans aged 36-60 years old who had been buried approximately 45-50 years ago. Solid structures which strongly resembled shrunken human brain tissue were found inside 2 intact skulls. Among other bones 5 similar structures were found one of which was an almost entirely preserved human brain, and the others were fragments from different regions of the human brain. Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 1 publication
5
24
0
Order By: Relevance
“…Similar findings were also reported in work on the brains of Inca mummies (Previgliano et al, 2003) where both the white matter and the grey matter were clearly discernible. In a cross-sectioned examination on a mummified brain by Radanov et al (1992), they also reported 'a distinguishable, non-uniformly outlined, thin outer band, greyishblack in color, suggestive of the cortex; and below a zone of whitish-grey color resembling the white substance of the brain'. Since we also found compartmentalised regions of grey and white matter in the cross-sections of the mummified brain that we studied, it can be said that the current case shares a common morphological pattern with those of previously reported cases of mummified brains.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Similar findings were also reported in work on the brains of Inca mummies (Previgliano et al, 2003) where both the white matter and the grey matter were clearly discernible. In a cross-sectioned examination on a mummified brain by Radanov et al (1992), they also reported 'a distinguishable, non-uniformly outlined, thin outer band, greyishblack in color, suggestive of the cortex; and below a zone of whitish-grey color resembling the white substance of the brain'. Since we also found compartmentalised regions of grey and white matter in the cross-sections of the mummified brain that we studied, it can be said that the current case shares a common morphological pattern with those of previously reported cases of mummified brains.…”
Section: Discussionmentioning
confidence: 94%
“…However, a contradictory view on the preservation of mummified brains has also been suggested. As an answer to the question of why brains have been preserved as mummified tissue even after all other tissues have disappeared, leaving only skeletal remains (Radanov et al, 1992), Hess et al (1998) speculated that myelin sheaths and collagen fibres show remarkable resistance to tissue disintegration. According to Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in an excellent morphological preservation showing gyri and sulci and main brain parts (hemispheres, hindbrain, medulla oblongata with the pons, etc.) (Padanov et al, 1992). The brain may in other circumstances liquefy postmortem, so that only a hardened ''rim'' along the inside of the skull remains.…”
Section: Methods In Mummy Researchmentioning
confidence: 99%
“…Adipocerous change is not uncommonly found in the brain, since brain tissue is also high in fat content. Thus well-preserved brains may be found even if all other soft tissue has decomposed (Tkocz et al, 1979;Radanov et al, 1992). Adipocire was previously thought to be a process of saponification of organic fatty acids in the presence of lime or calcium carbonate (Micozzi, 1991).…”
Section: Mummification Natural Mummiesmentioning
confidence: 96%